1999
DOI: 10.1002/(sici)1520-6327(1999)40:1<41::aid-arch5>3.0.co;2-r
|View full text |Cite
|
Sign up to set email alerts
|

Plasmatocyte spreading peptide does not induceMicroplitis demolitor polydnavirus-infected plasmatocytes to spread on foreign surfaces

Abstract: Capsule formation by the moth Pseudopulsia includens requires that plasmatocytes change from being nonadhesive cells in circulation to strongly adhesive cells capable of attaching to the foreign target and one another. This change in adhesive state is induced by Plasmatocyte Spreading Peptide (PSP1); a 23 amino acid peptide isolated from P. includens plasma. Plasmatocytes from hosts parasitized by Microplitis demolitor remain in a nonadhesive state after infection by Microplitis demolitor polydnavirus (MdPDV).… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
7
0

Year Published

1999
1999
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 39 publications
1
7
0
Order By: Relevance
“…Although the protein precursor of the ENF peptide is activated in a manner analogous to those with most of the neuroactive and other biogenic peptides (37), the latter events following activation of the cytokine precursor have been poorly understood in insects as well as mammals. In the last instar larvae of Lepidoptera, the proportion of immune potent cells such as plasmatocytes and granular cells is extremely high: the two cell types comprise greater than 90% of the total circulating hemocyte population in Pseudoplusia includens (13,38). If the hemolymph concentration of the ENF peptide continuously keeps high enough to activate these immune cells, the larvae would possibly suffer serious damages through unnecessary excessive stimulation of these cells.…”
Section: Discussionsupporting
confidence: 78%
“…Although the protein precursor of the ENF peptide is activated in a manner analogous to those with most of the neuroactive and other biogenic peptides (37), the latter events following activation of the cytokine precursor have been poorly understood in insects as well as mammals. In the last instar larvae of Lepidoptera, the proportion of immune potent cells such as plasmatocytes and granular cells is extremely high: the two cell types comprise greater than 90% of the total circulating hemocyte population in Pseudoplusia includens (13,38). If the hemolymph concentration of the ENF peptide continuously keeps high enough to activate these immune cells, the larvae would possibly suffer serious damages through unnecessary excessive stimulation of these cells.…”
Section: Discussionsupporting
confidence: 78%
“…Clark et al (1997) reported that PSP1 dosedependently induces plasmatocytes to spread on planer surfaces in vitro and to aggregate in vivo. Plasmatocytes responding to PSP1 are labeled by the mAb marker 43E9A10, whereas plasmatocytes that remain unspread in the presence of PSP1 are labeled by other anti-plasmatocyte mAbs (Clark et al, 1997;Gardiner and Strand, 1999;Strand et al, 1999). These results indicated that plasmatocytes consist of at least two subpopulations and that PSP1 affects the adhesive state of plasmatocytes recognized by mAb 43-E9A10.…”
Section: Psp1 Induces Plasmatocytes From Other Lepidoptera To Aggregatementioning
confidence: 93%
“…As noted in the preceding experiments, plasmatocytes readily spread on foreign surfaces like culture plates. In contrast, plasmatocytes and granulocytes do not attach or spread on cultures plates precoated with the basement membrane product Matrigel or agarose Pech and Strand, 1996;Strand et al, 1999). Addition of PSP1 to plasmatocytes in agarose-coated wells induced cells to rapidly aggregate.…”
Section: Psp1 Induces Plasmatocytes To Aggregate When Cultured In Agamentioning
confidence: 99%
“…Studies with several parasitoid-host systems have indicated that PDV-infected hosts do not mount an encapsulation response, which in turn allows the parasitoid's offspring to successfully develop (1,7,11,19,28,31,44). Hosts parasitized by the braconid Microplitis demolitor are unable to encapsulate parasitoid eggs or other foreign targets because hemocytes infected by M. demolitor bracovirus (MdBV) lose the capacity to adhere to foreign surfaces by 4 to 6 h postinfection (31,33). Hemocytes in primary culture and the hemocyte-like cell line BTI-TN-5B1-4 (High Five) from Trichoplusia ni also lose the ability to adhere to foreign surfaces after infection by MdBV (3,31).…”
mentioning
confidence: 97%